Construction de Variétés de Groupes Exceptionnels Non k-Rationnelles - Gille, Philippe (Mathematica Scandinavica, 2015)
Our goal is to construct non k-rational varieties of exceptional groups. The relevant invariant is the defect of weak approximation.